Quantification of microplastics in sediments from Narragansett Bay, Rhode Island USA using a novel isolation and extraction method. (January 2022) - Cashman, Michaela A.; Langknecht, Troy; El Khatib, Dounia; Burgess, Robert M.; Boving, Thomas B.; Robinson, Sandra; Ho, Kay T.
Abstract: Microplastics are small plastic particles found ubiquitously in marine environments. In this study, a hybridized method was developed for the extraction of microplastics (45–1000 μm) from sediments using sodium bromide solution for density separation. Method development was tested using spiked microplastics as internal standards. The method was then used to extract microplastics from sediments in Narragansett Bay, Rhode Island, USA. Suspect microplastics were analyzed with Raman spectroscopy. Microplastic abundance ranged from 40 particles/100 g sediment to 4.6 million particles/100 g sediment (wet weight). Cellulose acetate fibers were the most abundant microplastic. These results are some of the first data for microplastics in Rhode Island sediments. Graphical abstract: Unlabelled Image Highlights: Microplastic in Rhode Island, USA totaled 40–4.6 million pieces per 100 g sediment. Cellulose acetate fibers were the most abundant microplastic type. A novel method was used to extract microplastics from sediment.